2012
DOI: 10.1090/s0002-9947-2012-05510-3
|View full text |Cite
|
Sign up to set email alerts
|

The complex Green operator on CR-submanifolds of $\mathbb{C}^{n}$ of hypersurface type: Compactness

Abstract: Abstract. We establish compactness estimates for ∂ b on a compact pseudoconvex CR-submanifold of C n of hypersurface type that satisfies property(P). When the submanifold is orientable, these estimates were proved by A. Raich in [32] using microlocal methods. Our proof deduces the estimates from (a slight extension, when q > 1, of) those known on hypersurfaces via the fact that locally, CR-submanifolds of hypersurface type are CR-equivalent to a hypersurface. The relationship between two potential theoretic co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
7
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 39 publications
0
7
0
Order By: Relevance
“…Unfortunately, while the results of Theorem 1.1 do not depend on the metric, our condition appears to depend on the metric (see Proposition 6.3). See [Str11] for discussion of analogous difficulties surrounding the apparent metric dependence of Property (P q ). This is another benefit of working in generic Stein manifolds, since our example in Section 6 requires a non-Euclidean metric.…”
Section: Introductionmentioning
confidence: 99%
“…Unfortunately, while the results of Theorem 1.1 do not depend on the metric, our condition appears to depend on the metric (see Proposition 6.3). See [Str11] for discussion of analogous difficulties surrounding the apparent metric dependence of Property (P q ). This is another benefit of working in generic Stein manifolds, since our example in Section 6 requires a non-Euclidean metric.…”
Section: Introductionmentioning
confidence: 99%
“…where ( , ) = ( , ) + ( * , * ). For this estimate and further results on the compactness of the complex Green operator see, e.g., [16][17][18][19]. Applying (32) for Λ 1 , we obtain…”
Section: Theoremmentioning
confidence: 61%
“…In the case that M is a smooth, embedded, orientable CR manifold of hypersurface type, Raich showed that G q is compact if M satisfies (CR-P q ) and (CR-P n−1−q ) where (CR-P q ) is a CR version of P q . Straube later relaxed the orientability condition [21] and also showed the equivalence of P q and (CR-P q ) if M is orientable and pseudoconvex. Khanh, Pinton, and Zampieri later relaxed the embeddedness requirement [15].…”
mentioning
confidence: 99%